SAT0627-HPR Educational Needs of French Rheumatology Nurses Are Not Limited To Inflammatory Arthritis Management. Results of The Multicentric "Caire" Survey. (15th July 2016) - Beauvais, C.; Pouplin, S.; Mulliez, A.; Fayet, F.; Poilverd, R.M.; Gossec, L.; Perrot, S.; L'Amour, C.; Mezières, M.; Aubert, M.P.; Jaccaz Vallée, N.; Savel, C.
Abstract : Background: EULAR recommendations aim to promote the role of the nurse in the management of inflammatory arthritis (IA) (1). A survey among French nurses in 2014–2015 showed a gap between educational needs and reported competences of French nurses regarding IA management (2). Objectives: The objective was to investigate competencies in other rheumatic and musculoskeletal conditions (RMD), patient education and research compared with those found in IA. Methods: The list of potentially useful competencies for RN was validated by a multidisciplinary group (2). The survey was conducted through 3 on-line quesitionnaires in Dec 2014-Jan 2015 (2) then in Jan-May 2015, including 78, 72, 70 items. For each item, the RN were asked on a 4 point likert scale if they believed they had acquired the competency and considered it of importance. Results: All RMD were adressed: rheumatoid arthritis RA, spondyloarthritis SpA, connective tissue diseases (CTD), other RMD e.g osteoarthritis, osteoporosis, low back pain. The cross-functional skills were pain management, patient-nurse communication, patient education, research. Respectively 104, 71 et 64 RN responded the 3 on-line investigations, 92% female, 70% worked full time, 70% in a university hospital; 30–29% declared qualifications in patient education, 9–20% in pain management, 6–17% in research. Reported competencies were very good in DMARDS, analgesics and NSAIDs, good in patient-nurse communication and patient education. In other fields, educational needs are high, particularly for non-pharmacological treatments, CTD, osteoarthritis, low back pain and research (table). Practical skills were less than cognitive skills. Conclusions: This multicentric survey provides accurate information on French RN educational needs. They are greater in the management of RMD other than RA and SpA. These results should be considered in elaborating a curriculum to improve RN competencies. References: van Eijk-Hustings Y et al. Ann Rheum Dis. 2012;71:13–9. Beauvais Ann Rheum Dis 2015;74(Suppl2):1326. Acknowledgement: Members of the committee for the French Rheumatology Nurse educational course Disclosure of Interest: None declared